AI Health Literacy vs. Traditional Education: A New Imperative for Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
AI Health Literacy vs. Traditional Education: A New Imperative for Digital Health The rapid integration of Artificial Intelligence (AI) into healthcare ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning